COVID-19: Terapi Penghambat IL-1 dan IL-6 - Hendra H (JURNAL IMPLEMENTA HUSADA, 2021)
Abstract: As of February 2021, there are 102,817,575 cases of COVID-19 globally, causing 2,227,420 deaths, and has been declared as pandemic by WHO. Over time, the management of COVID-19 has evolved, namely the use of Interleukin (IL). Patients with severe COVID-19 experience a hyper-inflammatory response to the virus, called "cytokine storms". Cytokine storms are thought to occur due to the excessive release of pro-inflammatory cytokines such as IL-1?, IL-6, IL-18 and interferon-?. In hyperinflammatory conditions, therapy with cytokine-blocking agents such as IL-1 inhibitors (Anakinra) and IL-6 inhibitors (Tocilizumab) is quite promising. Anakinra has the effect of lowering il-6 production, its because IL-1 is a potential inducer for IL-6, so the Tocilizumab effect is also seen in Anakinra. Anakinra has a short half-life, so the undesirable effect can stop immediately. However, interleukin therapy still requires further research related to the efficacy and safety of the drug.Keywords: COVID-19, IL-1 inhibitor, IL-6 inhibitor, Anakinra ,Tocilizumab